Situation Report: Hungary, 27 April 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Plenum Discusses Foreign Affairs and Domestic Economy Decree on Procurement, Recruiting, and Redirection of Labor Polish Construction Enterprise Gains Another Hungarian Contract World Federation of Hungarians Preliminary Report on the Agricultural Co-operatives in 1975 Milk Yields and Private Plot Taxation An Educational Experiment Criticized